A family affair - Michaels, Fern (New York : Kensington Publishing Corp., 2014)
In a city built on dreams, Trisha Holiday makes her living moving like one. But out of her dancer's costume, she's as down-to-earth as they come. That's why she ignores the admiring note--and the accompanying $1000 bill--that arrives backstage after one of her ethereal performances. Yet the sender, a wealthy foreign prince, isn't easily dissuaded.
Keywords: Dancers -- Fiction; Princes -- Fiction; Families -- Fiction; Sisters -- Fiction; Life change events -- Fiction